Spontaneous omental hematoma - Bhandari, RS; Sapkota, R; Mishra, P; Singh, KP (Journal of Institute of Medicine Nepal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Spontaneous omental bleeding is a rare entity, and usually presents with various combination of sudden abdominal pain, shock, peritonitis and hemoperitoneum. A 68 year female presenting with acute abdomen and without antecedent trauma had obscure hemoperitoneum. Exploration revealed hemoperitoneum and hemorrhagic omentum with a huge clot. Key Words: Spontaneous omental hematoma, acute abdomen, hemoperitoneum, surgery. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, April, 2009; 31:1 20-22